2012
DOI: 10.1111/j.1757-1707.2012.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

The sugar, biomass and biofuel potential of temperate by tropical maize hybrids

Abstract: The demand for biofuels has created a market for feedstocks to meet future energy requirements. Temperate 9 tropical maize (Zea mays L.) hybrids, which combine high biomass and fermentable stalk sugars, have yet to be considered as a biomass feedstock. Our objective was to evaluate biological potential, genetic variability and impact of nitrogen (N) on biomass, stalk sugar, and biofuel potential of temperate 9 tropical maize (TTM) hybrids. Twelve TTM hybrids, two grain and silage hybrids were grown in 2008, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…This suggests changes in the amount of major plant constituents such as lignin, cellulose, and hemicellulose. Similar results were noted for leaves, although differences were smaller than in stalks probably due to large reserve storage capacity in stalks (White et al, 2012). Furthermore, the higher C concentration in stalks was expected since these cultivars seem to favor strengthening these structures to support the weight of ears; this was especially true for single cross hybrids that combine small size with high production (Duvick et al, 2004;Santos et al, 2012).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This suggests changes in the amount of major plant constituents such as lignin, cellulose, and hemicellulose. Similar results were noted for leaves, although differences were smaller than in stalks probably due to large reserve storage capacity in stalks (White et al, 2012). Furthermore, the higher C concentration in stalks was expected since these cultivars seem to favor strengthening these structures to support the weight of ears; this was especially true for single cross hybrids that combine small size with high production (Duvick et al, 2004;Santos et al, 2012).…”
Section: Resultssupporting
confidence: 66%
“…That is, double cross hybrids and triple cross hybrids offset the effect of drought on cob production by increasing stalk and leaf production, which practically does not occur with the single cross hybrids. This increase is due to alterations in the source/sink photoassimilates, given that the reduction in the amount of sinks (grain) may favor photoassimilates storage in stalks and leaves (Lee;Tollenaar, 2007;White et al, 2012). In practical terms, this indicates that certain cultivars have greater secondary use potential (i.e., animal feed or energy production) in case of severe damage to the main use (grain production).…”
Section: Resultsmentioning
confidence: 99%
“…A previous research indicated that temperate-tropical hybrids could adapt to more diverse growing environments than temperate-temperate or tropical-tropical hybrids72. A biofuel potential investigation with 12 temperate-tropical maize and two grain and silage hybrids indicated that temperate-tropical hybrids showed more stalk biomass and 50% more sugar with supplemental fertilizer N, and could produce equivalent ethanol with a small amount of nitrogen fertilizer73.…”
Section: A Maize Multiple Hybrid Populationmentioning
confidence: 99%
“…Nonetheless, stover residues are essentially a no‐cost supplement that can augment yield 2. Varieties of maize and its close relative sorghum that are photoperiod sensitive grow larger, flower later, require minimal N inputs since they produce little or no grain, and can provide as much or even more biomass than Miscanthus in most dry locations 13,15,21–24. Sorghum is grown on about 4.8 million US acres, primarily for livestock grain and forage mainly in the Great Plains states in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Photoperiod‐sensitive maize hybrids derived from crosses of tropical and temperate‐adapted varieties are another underexploited source of germplasm for generating varieties optimized for sugar and biomass that give high productivity with low nitrogen inputs (Table 1). 23,24…”
Section: Introductionmentioning
confidence: 99%